Multiple-scale Temporal Variability of Climatic Time Series in the Western Region of Iran - Abolfazl Neyestani (Sustainable Earth Trends)
The current research aims to carry out a multi-timescale variability analysis for the time series of sunspots (SN), precipitation (Pr), and maximum temperature (Tmax) in four main stations in the western area of Iran. In addition, the emphasis is on the impact of the decadal solar cycle on the variability of climatic quantities. Appropriate statistical methods were employed to investigate the relationships between reconstructed time series. The results demonstrated that the more intense intra-annual to inter-annual fluctuations of the SN signal are synchronized with the peak of the decadal component of sunspots. For the monthly precipitation, the deviation from the regular yearly pattern is markedly related to intense intra-annual variations in comparison to the inter-annual plus decadal variations. While the dominant mode of variability of the SN, which contains 89% of the variance, occurs at low frequencies according to cumulative spectral power (CSP), the contribution of this band in the variability is less than 10% for the Pr and is trivial for the Tmax. The result of wavelet coherence (WTC) analysis indicates a close connection between the variability of Tmax and Pr at different timescales over the region, except for the 32-128-month scale, which is free of significant common oscillations. Furthermore, a signature of a significant decadal fluctuation was also observed between Tmax and Pr which shows a completely different phase relationship for this timescale when compared to all smaller scales.